2010
DOI: 10.1111/j.1365-4632.2009.04390.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary syphilis resembling erythema multiforme

Abstract: One should consider secondary syphilis in the differential diagnosis of an eruption resembling EM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…2,3,[5][6][7][8][9][10] One case had plasma cell infiltrate, but silver stain for T. pallidum in the section was negative. 4 Our patient could have both EM and EM-like syphilitic lesions as he did not have plasma cell infiltrate indicative of secondary syphilis, had a histology suggestive of EM and positive IHC staining for T. pallidum. The mechanism involved in the T. pallidum-induced EM is unclear.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…2,3,[5][6][7][8][9][10] One case had plasma cell infiltrate, but silver stain for T. pallidum in the section was negative. 4 Our patient could have both EM and EM-like syphilitic lesions as he did not have plasma cell infiltrate indicative of secondary syphilis, had a histology suggestive of EM and positive IHC staining for T. pallidum. The mechanism involved in the T. pallidum-induced EM is unclear.…”
Section: Discussionmentioning
confidence: 71%
“…To our knowledge, there are only ten cases of EM-like secondary syphilis published in the literature since 1999 (Table 1). [2][3][4][5][6][7][8][9][10][11] Among these cases, only three were coinfected with HIV. 2,5,9 Our patient had typical targetoid skin lesions, some were bullous, as in cases 5 and 9.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to recognize rare clinical presentations of syphilis may delay diagnosis and treatment, and moreover enable further transmission. 2,10,12 We conclude that syphilis screening should be recommended in erosive interdigital lesions negative for fungal infections, especially in individuals at risk of acquiring HIV and STIs.…”
Section: Discussionmentioning
confidence: 93%
“…Several recent case studies have suggested that targetoid lesions similar to those seen in this patient could be a novel presentation of EM caused by a reaction to the syphilis, as opposed to simply an unusual presentation of secondary syphilis. 3 The exact pathophysiology of EM is not well understood, but it is likely a type of hypersensitivity reaction. The clinical presentation in this patient of targetoid lesions was EM-like and many of the pathology changes, including vacuolar degeneration of basal layer keratinocytes and interface dermatitis seen on this patient's biopsy result, can be seen in both syphilis and EM.…”
mentioning
confidence: 99%
“…4 Four previously described patients exhibited targetoid lesions in their presentations of secondary syphilis, suggesting that this is not an isolated unique event and may link EM and T pallidum. 3,4 After hitting a low point in 2000, US cases of syphilis have been steadily increasing during the past decade, with only a slight decline in 2010. 5 With the ever-changing clinical presentation, it is important for physicians in all practices, including pediatrics, to have a low threshold for testing for syphilis in patients with unusual skin findings.…”
mentioning
confidence: 99%